Training and education for network centric warfare : issues for New Zealand's Defence Force : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Defence and Strategic Studies at Massey University - Currey, Eden Douglas (Massey University, 2006)
The concept of Network centric warfare (NCW) is viewed as the next revolution in military affairs. Its introduction globally will necessarily affect the way the New Zealand Armed Forces operates in future conflicts. With the increasing use of digital technology in the military environment the need for and degree of increasing knowledge of Network Centric Warfare and its concepts must be explored.This country will have to combine its own definition and understanding of NCW into the framework of its Armed Force if it wants to continue to remain interoperable with technologically advanced coalition forces. This thesis looks into the issues and solutions which have been considered by other countries in their attempts to implement the NCW concept. It examines in detail how issues and solutions could be applied to New Zealand's attempt at NCW. Chapters One and Two define the academic processes which have been used in this study. They also give a brief introduction to the broad idea of Network Centric Warfare and its origins. Chapter Three examines in detail the complex evolution of the concept of Network Centric Warfare to its present state. In particular, it looks at how the events of September 11th 2001 have redefined warfare and the impact of that revolution on the traditional NCW concept. This chapter also focuses on the advantages and disadvantages of NCW which have now been proven through the experiences of Operation Enduring Freedom and Operation Iraqi Freedom. These two conflicts have been described as the first information technology wars of the 21st century. Chapter Four focuses on how the concept of Network Centric Warfare has and will affect the specifics of personnel and make-up of the New Zealand Defence Force, as it makes the transition from a Platform centric to a Network Centric approach in warfare. The special focus in this chapter is on the New Zealand Army. The concepts of the ethos and cultural identity of a force are introduced here, with a view to revealing the influences that the adaptation of NCW methods and techniques can have on the organisation of that force. The discussion concludes that the introduction of NCW can have profound and permanent effect on a force's ethos and identity. This chapter also considers the influence of technology can help in the recruitment and retention of highly skilled people in the Army. Chapter Five shows how the adoption of the concept of Network Centric warfare also has the potential to fundamentally change the way in which higher level policy and doctrine are introduced and modified in the Armed Forces. This chapter looks at how future infrastructure and policies will need to have increased flexibility built into them from the start in order to embrace the demands of NCW for rapid developments in information technology and force-wide diffusion of such developments. Chapter Six discusses a third important consequence of adopting the concept of Network Centric Warfare. Namely, how the introduction of NCW will affect both training and education of service personnel. In particular, it examines how the change from Platform Centric to Network Centric forms of warfare puts changing demands on the skill sets and needs required of service personnel. Examples are given of the new skill sets needed in order for them to work effectively in a NCW environment. Chapter Seven discusses the formation of a new training branch of service which will need to be set up to accommodate the new methods and skills that NCW brings to the battlefield. Included in this chapter are the imperatives of Information Warfare, Electronic Warfare, and Computer Network Operations for such a branch. Alongside Air, Land, Sea and Space NCW brings with it the creation of a fifth battle space. This battle-space is cyberspace which encompasses the electromagnetic sphere, the Internet and all manner of Wide and Local Area Networks (WANs and LANs). Chapter Eight returns to the issue of training and education introduced in Chapter Six, but focuses specifically on the use of simulation techniques and technologies. Such techniques will be required in order to help train soldiers to work effectively and efficiently under NCW. Why other training methods won't work well given an NCW environment, and why simulation technologies will work, is explained with examples of each. This chapter argues in particular that simulation provides the most effective training in the unified data architecture that will be needed to provide cross platform capability and inter and intra service solutions in Network Centric Warfare. Examples of data solutions are provided to help explain the underlying simulation concepts and methods. Chapter Nine is the conclusion of this study. It reviews the results of this thesis and provides recommendations on the implementation of the Network Centric Warfare environment required in the New Zealand Armed Forces.
Keywords: Military education; New Zealand; Military art and science; Armed forces -- Training of